2019
DOI: 10.1186/s12885-019-5565-9
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of circulating extracellular vesicles and biomarker discovery associated with treatment response in head and neck squamous cell carcinoma

Abstract: Background There is a paucity of plasma-based biomarkers that prospectively segregate the outcome of patients with head and neck squamous-cell carcinoma (HNSCC) treated with chemoradiation therapy (CRT). Plasma extracellular vesicles (EVs) might be an alternative source for discovery of new specific markers present in patients with HNSCC, which could help to re-direct patients to appropriate curative therapies without delay. Methods In order to identify new markers in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…However, the roles of the miRNAs mentioned above have not been validated due to lack of plasma samples [41]. In addition, it was identified that hsa-miR-125b-5p, as a T-cell suppressor, had an [86] increasing trend in the PD group at baseline and was significantly decreased in plasma EVs of PR patients after treatments [41]. It is thought that down-regulation of hsa-miR-125b-5p in EVs during treatment may imply an increased T-cell function of patients and a favourable response to immunotherapy [41].…”
Section: Circulating Ev-mirnas In Lung Cancermentioning
confidence: 99%
“…However, the roles of the miRNAs mentioned above have not been validated due to lack of plasma samples [41]. In addition, it was identified that hsa-miR-125b-5p, as a T-cell suppressor, had an [86] increasing trend in the PD group at baseline and was significantly decreased in plasma EVs of PR patients after treatments [41]. It is thought that down-regulation of hsa-miR-125b-5p in EVs during treatment may imply an increased T-cell function of patients and a favourable response to immunotherapy [41].…”
Section: Circulating Ev-mirnas In Lung Cancermentioning
confidence: 99%
“…The subsequent validation of EV proteins obtained from media supernatant in clinical samples demonstrated the ability of the organoid platform to enable the identification of cancer biomarkers for PDAC patients. Moreover, recent evidences suggest EVs potential role in early disease detection (Melo et al, 2015) and prediction of response to treatment (Ciravolo et al, 2012;Wei et al, 2014;Rodrigues-Junior et al, 2019). The ability to enter other cells and deliver a functional cargo, even at distant sites, without inducing toxicity makes them good therapeutic agents vehicles (Ferguson and Nguyen, 2016).…”
Section: New Horizons Of Organoids Application: Modeling Evs Releasementioning
confidence: 99%
“…Rodrigues-Junior et al analyzed the ability of exosomes to predict therapy outcome by analyzing pooled plasma samples from locally advanced HNSCC patients who had complete or incomplete response to chemoradiation therapy [89]. They identified a different proteomic profile between exosomes derived from responders and nonresponders.…”
Section: Exosomes As Biomarkers and Players In Response To Therapy Anmentioning
confidence: 99%